A mineralogical evaluation of the spiral circuit at the Mount Wright concentrator by image analysis - J. M. D. Wilson; W. Petruk; C. Coté (Canadian Institute of Mining, Metallurgy and Petroleum, 1990)
"The behaviour of minerals in the Mount Wright spiral circuit was investigated to find methods of improving iron oxide mineral liberation and recovery. The feeds, concentrates and tailings from rougher, cleaner and recleaner spirals in one mill line were sampled before and after the sizing screen openings were reduced from 2 mm to 1.6 mm. Sized fractions of each sample were analyzed with the MP-SEM-IPS image analysis system at CANMET to determine mineral quantities and liberation characteristics of the iron oxide minerals. Mass balance techniques were used to calculate stream recoveries of iron, silica, total iron oxide minerals, hema¬tite, goethite, quartz, ferromagnesian silicates, and liberated and locked total iron oxide minerals for each sieve fraction.The reduction of the sizing screen openings increased the ap¬parent liberation of the total iron oxide minerals in the screen undersize from 89% to 94% and raised the over-all iron recovery from 84.4% to 85.3%. Apparent liberation of iron oxide minerals in the cleaner sand also increased from 70% to 85%, but the – 75 µm fraction re¬mained the only fraction containing an acceptable amount of liber¬ated iron oxide minerals in each case. Due to limitations of spiral and grinding efficiency it is recommended that the cleaner sand be screened at 300 m, the +300 m fraction be reground, and the – 300 p.m fraction be rerouted to the rougher spirals.The amount of fine liberated iron oxide minerals (– 106 m) lost in the tailings was 46 TPH in mill line 3. This value represents 41 wt % of the free fine iron oxide minerals, or 7 wt % of the total iron oxide minerals in the spiral feed. Further work is needed to investigate the possibility of recovering this material by other methods.Middling iron particles (010 50%) and presumably free gangue in the size range –300+ 75 m tend to be recovered by spirals by entrapment."